Analisis Lingkungan Pemasaran dalam Menentukan Strategi Pengembangan Usaha pada UMKM Pondok Al-Azka - Nurhalizah Nurhalizah; Luthfiyyah Luthfiyyah; Alfitra Nurhikma B; Muhammad Adriansyah; Syafar Ahmad (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the marketing environment of Pondok Al-Azka to identify strategic opportunities and threats affecting business sustainability in the competitive housing market of Makassar. A qualitative descriptive approach was employed, utilizing case study methods and data collection through in-depth interviews and direct observations. The research findings reveal that Pondok Al-Azka possesses a significant competitive advantage through a penetration pricing strategy and extensive parking facilities, which are crucial factors for the student segment. However, the business faces substantial external threats, including high dependence on the academic calendar of Universitas Negeri Makassar and a shift in consumer preferences toward digital connectivity. Analysis of the marketing mix indicates that while low rental costs maintain local stability, the lack of digital visibility limits broader market reach. The study concludes that Pondok Al-Azka is currently in a stable yet vulnerable position. To ensure long-term growth, the business must transition from conventional to hybrid marketing strategies by integrating digital visibility via Google Maps and providing Wi-Fi facilities. Internal management improvements regarding cleanliness and order are also essential to enhance service quality. These strategic steps are vital for maintaining student loyalty and competing with modern housing alternatives in the digital era.